De uma questão preliminar a toda abordagem educacional na psicose: a inclusão da foraclusão - Costa, Vinícius Amaral (2019)
Reality as psychic reality, unlike a natural or “external reality”, has always been a notion since Freud, and still is a topic of debate among contemporary authors. We see in the impasses of inclusive education questions regarding the relation of the child with reality. The norm is the parameter of regency through an operation that, symbolically, brings segregation as consequence: those who are in agreement with this functioning are divided from those who are not. The theory of psychosis in Lacan, from the schemas presented in the text “From a preliminary question to any possible treatment of psychosis”, could contribute to the dialogue of psychoanalysis with the educational field? It is discussed the importance of the place of signification for the child as an act of subjective constitution, from speech and with the Other. A typical signification to psychosis can bring impasses in the encounter of this structure with the norm since it takes the particularity of being structurally governed by the forclusion of the Name-of-the-Father, concept that guides us to think the symbolic functioning in the psychosis